Dissolved and soluble pore water trace metals (Mn, Fe, Co, Ni) from sediment core SO268/2_171-1 (MUC-31) during SONNE cruise SO268/2, central Pacific - Schmidt, Katja; Paul, Sophie Anna Luise; Achterberg, Eric Pieter (In: Paul, Sophie Anna Luise; Schmidt, Katja; Achterberg, Eric Pieter; Koschinsky, Andrea (2024): Pore-water and solid-phase trace metals from sediment cores during SONNE cruises SO268/1 and SO268/2, central Pacific [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.965035, 2022)
Physical and chemical trace metal speciation are important for our understanding of metal cycling and potential toxicity to marine life. Trace metals can have different bioavailability and behave differently in diffusion processes or particle-solution interactions depending on their physical and chemical forms. Here we investigated dissolved (< 0.2 µm) and soluble (< 0.02 µm) concentrations of Mn, Fe, Co, and Ni in oxic deep-sea sediments of the central equatorial Pacific. The colloidal fraction (> 0.02 µm < 0.2 µm) of Mn, Co, and Ni increased with depth in the oxic pore waters and Fe had the largest but variable colloidal pool. Samples were taken during the SO268 cruise to the German and Belgian license areas for polymetallic nodule mining in the Clarion Clipperton Fracture Zone as part of the MiningImpact project. Sediment cores were collected with multicorers (MUC) and ROV push cores (PUC). Pore water was extracted by means of centrifugation and sequential filtration using cleaned polyethersulfone (PES) syringe filters (0.2 µm) and Anopore syringe filters (0.02 µm). Pore water was preserved by acidification to ~ pH 1.8 with concentrated ultrapure HCl. Samples were preconcentrated offline with seaFAST and measured by High Resolution Sector Field Inductively Coupled Plasma-Mass Spectrometry.
Keywords: CCZ; Pacific; pore water; size fractionation; trace metals